A Morpho-Syntactic Analysis of Agreement Patterns in Pashto and English - Rahman, Gohar; fitriyah, Aidatul (Indonesian Scientific Publication, 2024)
This research explores the subject-verb agreement system of Pashto and English, focusing on their syntactic and morphological properties. Pashto belongs to the group of Indo-Iranian languages, characterized by a sophisticated agreement system with verbs inflected for number, person, and gender, particularly in past and future tenses. In contrast to Pashto, the English language has a simpler agreement system with minimal inflection. This study explores various approaches to grammatical agreement and their implications for language learning and theoretical linguistics by comparing the subject-verb agreement of both languages. A comparative linguistic approach was employed, utilizing a qualitative method. Data were collected from written and spoken sources in both languages, followed by systematic syntactic analysis. The findings of this study show apparent discrepancies in the agreement system of Pashto and English Languages. Pashto has a complex agreement system involving a rich inflection for number, person, and gender, showing a loaded morphological structure. This inflectional richness of Pashto provides multifaceted information that supports accurate and clear communication. In contrast, English has a more streamlined agreement system with simpler inflection. Moreover, the findings contribute to the knowledge of cross-linguistics variations and offer information for language education in multilingual contexts.